Makna Kefaan Hidup dalam Mazmur 39:6-7 dan Implikasinya bagi Kehidupan Modern - Mey Pasampe; Esrawati Ka’bi Sumussang; Arya Salo Pongtinggi (Damai : Jurnal Pendidikan Agama Kristen dan Filsafat, 2026)
The fleeting nature of human life constitutes a key theme in theological reflections within the Old Testament, particularly in the Book of Psalms in the Alkitab, which highlights human limitations and the inherent uncertainty of existence. Psalm 39:6–7 depicts human life as a transient shadow and emphasizes the futility of human efforts if they are not oriented toward God. This study seeks to explore the meaning of human transience in this passage and assess its theological significance for contemporary life. A qualitative approach with biblical hermeneutics is employed, considering historical, literary, and theological dimensions. The analysis indicates that the metaphor of the “shadow” illustrates human fragility, while the depiction of life’s futility critiques the human tendency to find purpose solely in worldly endeavors. Despite this, Psalm 39 ultimately directs readers toward hope in God, portraying Him as the ultimate source of true meaning. In a modern, materialistic context, this message continues to be relevant as a reminder of human dependency on God and the limitations of human life. Therefore, the transience of life does not signify the end of existential purpose but rather opens the way to deeper spiritual insight and the strengthening of faith.